2015
DOI: 10.5194/isprsannals-ii-3-w5-369-2015
|View full text |Cite
|
Sign up to set email alerts
|

An Iterative Inference Procedure Applying Conditional Random Fields for Simultaneous Classification of Land Cover and Land Use

Abstract: ABSTRACT:Land cover and land use exhibit strong contextual dependencies. We propose a novel approach for the simultaneous classification of land cover and land use, where semantic and spatial context is considered. The image sites for land cover and land use classification form a hierarchy consisting of two layers: a land cover layer and a land use layer. We apply Conditional Random Fields (CRF) at both layers. The layers differ with respect to the image entities corresponding to the nodes, the employed featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…For classifying land cover and land use, we apply the contextual classification method presented (Albert et al, 2015), where a detailed description of the approach can be found. The approach performs a simultaneous classification of land cover and land use while considering semantic as well as spatial context.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…For classifying land cover and land use, we apply the contextual classification method presented (Albert et al, 2015), where a detailed description of the approach can be found. The approach performs a simultaneous classification of land cover and land use while considering semantic as well as spatial context.…”
Section: Methodsmentioning
confidence: 99%
“…In (Albert et al, 2014) we presented a two-step land use classification approach which was extended to include an iterative inference procedure in (Albert et al, 2015). In both approaches, CRFs are applied separately for land cover and land use classification.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations